Effective Visual Media to Increase Knowledge and Comprehension of Multidrug Resistant Tuberculosis Among Patients and Their Caregivers - Lidya Chaidir; Dyshelly Nurkartika Pascapurnama; Claudia Selviyanti; Cindy Natasha; Muti'ah Nurul Jihadah; Prayudi Santoso (Majalah Kedokteran Bandung, 2023)
Indonesia ranks thirdamong countries with the largest number of TB cases after India and China. Globally, more than 3-4% of all TB cases are Multidrug-Resistant Tuberculosis (MDR TB). MDR TB is a more complicated TB that needs extra treatments, which extend treatment time and increase adverse effects. Thus, MDR TB patients and their families often feel demotivated about completing treatment, leading to loss to follow up, which contributes to the never-ending transmission and greatly affects the success rate of the national TB control program. Thus, better knowledge and perception on MDR treatment for patients and families plays a crucial role in dealing with this issue. A cross-sectional study was performed from April to June 2019 to evaluate the effectiveness of visual educational media for TB patients and their caregivers. Participants consisted of 144 patients diagnosed with MDR TB and their caregivers or family members (n=22). A pre-test was administered before an education session by a nurse and visual media were used as the educational material. At the end of the session, a post-test was performed. The post-test score was then compared to the pre-test score to evaluate the session’s effectiveness using the paired t-test. Result showed significant increase in the post-test score (t= 3.249, df=3, p=0.04), with the caregivers attained a higher score, showing better improvement in knowledge after the session compared to the patient group. Hence, the MDR TB educational intervention using visual media is considered effective to increase participants ‘understanding of MDR TB. It is expected that with increased knowledge on MDR TB, the treatment success rate will increase and becomes the catalyst for the nationwide TB control strategy.